Study of the germination of seeds of some types of Laurus nobilis L. spread in different regions of Lattakia Governorate and its morphological characterization - عدره, ولاء (Latakia University Journal -Biological Sciences Series, 2022)
The study was conducted on 4 species of Laurusnobilis L. in the year 2021 in the three sites of Lattakia Governorate : WadiQandil, Al-Basset and Albahlolia. These spices were characted morphologically depends on 9 character for leaves and fruits . for germination tests we used three agricultural substrates : a. Altorf (T): b. Nursery soil (S): c. mixture of Altorf and Nursery soil (TS) by (1: 1). Morphological analysis shows a genetic variation between of 19-56%. the cultivars were divided into two groups . the first included the spices (S1 and S4) compared to 41%, the second included the spices ( S2 , S3) compared to 32%. The results showed that the Altorf has played its role in the suitability of the studied species both in terms of germination or in terms of continued growth and development, and also significant differences in the soil medium. Altorf Improved The data and indicators measured at the soil medium alone compared to the mixture at the level of physical, chemical and biological characteristics.